Optimization of Google Classroom in Blended Learning in Junior High School - Ishak Talibo; Pandu Adi Cakranegara; Muhammad Asrori Muazar Habibi; Faisal Faisal; Elhefni Elhefni (STAI Hubbulwathan Duri, 2022)
This study aims to optimize the learning of Islamic Religious Education with Google Classroom. This type of research is quantitative. The population as well as the sample is 4 teachers. Data was collected by means of a questionnaire via Google Form. Assessment of the questionnaire using the Guttman scale. Next is the interpretation of the calculation results. This study shows that the teacher's perception, ease of access, and the benefits of Google Classroom are on average 4.15 or 83.18%, this indicates that it is very good. Thus, Google Classroom can optimize online learning in blended learning on Islamic Religious Education subjects. This study recommends teachers to use Google Classroom in online learning or distance learning as an alternative application.